PHYSICIAN’S CIVIL LIABILITY IN PUBLIC HEALTH PRACTICE - Moreira Barcelos De Souza, Elizangela; Villela Florêncio, Stella (Revista Gênero e Interdisciplinaridade, 2023)
The objective of the present work is to analyze the civil liability of the doctor as a public agent or exercising a function in private law companies that provide public services. Detailing in a detailed way the requirements for the configuration of civil liability: conduct, damage and causal link, as well as the hypotheses of exclusion of liability, their nature, and the species of medical errors, especially medical acts performed in public health. Analyzing the possibilities of solidary legitimacy of the State and of the causative agent under the obstacle of the procedural economy and the institute of the denunciation of the dispute. In this way, the jurisprudential research was the method used to evidence the kind of legitimacy and the consequences of civil liability. Being demonstrated, the applicability of Theme 940 of the Federal Supreme Court, to remove the solidary legitimacy of the public agent causing the damage in the civil liability claim against the State, ensuring the right of return, for analysis of intent or fault. It is noted that the jurisprudential research evidenced the filing of actions with the qualification of the defendant considered illegitimate, since the State objectively responds for the acts of its agents. Thus, it is concluded that the objective civil liability of the doctor in the provision of medical services to public health, removes its legitimacy in the passive pole of the indemnity action; regressive action being applicable to them, after any eventual desire by the State.